2000
DOI: 10.1067/mva.2000.110053
|View full text |Cite
|
Sign up to set email alerts
|

Does the endovascular repair of aortoiliac aneurysms pose a radiation safety hazard to vascular surgeons?

Abstract: Although the total effective body doses under lead fell within established ICRP occupational exposure limits, they are not negligible. Because radiation exposure is cumulative and endovascular procedures are becoming more common, individuals performing these procedures must carefully monitor their exposure. Our results indicate that a team of surgeons can perform 386 hours of fluoroscopy per year or 587 EAIA repairs per year and remain within occupational exposure limits. Individuals who perform these procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 16 publications
(17 reference statements)
1
45
0
1
Order By: Relevance
“…Several studies have reported radiation exposure among vascular surgeons involved in fluoroscopy-assisted surgery [14][15][16], and found exposure to be within safe recommended limits.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported radiation exposure among vascular surgeons involved in fluoroscopy-assisted surgery [14][15][16], and found exposure to be within safe recommended limits.…”
Section: Discussionmentioning
confidence: 99%
“…Typical staff dose readings for different types of procedures have been published in the literature [11,19,[26][27][28][29][30][31][32][33][34][35][36]. Depending on the type of procedure and the technique used, the operator dose, per procedure, ranges from 3 to 450 lSv at the neck over protective garments, from\0.1 to 32 lSv at the waist or chest under protective garments, and from 48 to 1280 lSv at the hand.…”
Section: Surveillance Of Occupational Dosementioning
confidence: 99%
“…Despite the increasing caseload for many vascular surgeons and interventional radiologists [17,18], there are few studies that have specifically investigated the radiation exposure to the entire operating team. Radiation exposure to the medical staff is highly dependent on their position with respect to the patient couch.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%